Development of a Chemistry Enrichment Book Based on STEAM-Integrated Project based learning for Grade XII Students: Development of a Chemistry Enrichment Book Based on STEAM-Integrated Project based learning for Grade XII Students - Meli Sartika Silaban; Nurfajriani Nurfajriani; Jamalum Purba; Saema Saema (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The development of governance and learning tools from 2022 to 2025 has shown significant improvement, as evidenced by the ministry of education, culture, research, and technology's programs, such as the national book writing school movement and "literacy for the golden generation". This study aims to develop a chemistry learning book that is appropriate and effective, and can support the implementation of chemistry learning. The type of research used is development and research, with the ADDIE model, but due to time constraints, this study only reached the development stage. Validation of the developed enrichment book was carried out by three chemistry lecturers and three teachers using instruments that comply with the national education standards agency standards. Based on the validation results, the average value of the content feasibility test was 3.70 (92.5%), the average language feasibility test was 3.81 (95.25%), the average presentation feasibility test was 3.64 (91%), the average presentation graphic feasibility test was 3.78 (94.5%), the average STEAM implementation feasibility test was 3.81 (95.25%). The STEAM-integrated PjBL-based enrichment book has met the modified national education standards agency standards and the feasibility criteria, with validation results averaging 3.74 (93.5%) in the very suitable category as a learning support book. In the book, there are enrichment questions that have been validated by material experts and through field trials, the calculated t data> t table with a t table of 2.06, so the questions are included in the valid category